The Effect Of Compensation, Work Motivation, And Workload On Employee Performance Employees At Pt Giken Precision Indonesia - Herayanti, Pesi; Soleh, Ahmad; Abi, Yudi Irawan (Universitas Dehasen Bengkulu, 2024)
This research uses a type of descriptive research in explaining the influence of compensation and work motivation on employee performance. This type of research is a quantitative research method. Research is a systematic method that aims to provide information in solving problems in the variables being studied while quantitative methods are methods used to generalize populations and samples that have been determined as hypothesis tests. From the significance value shows that X1 (compensation) has a positive and significant effect on Y (employee performance) Pt Giken Precision Indonesia.. With tsig value < a (0.001< 0.05) and thitung value > ttable (4.654>1,676). Variable X3 (motivation) has a positive and significant effect on Y (employee performance) of Pt Giken Precision Indonesia. With the value of tsig < a (0,038<0,05) and the value of thitung>ttable is obtained ( 2.131>1,676). From the significance value of the Burden variable (X3) has a negative effect and does not significantly affect employee performance (Y). With the value of tsig < a (0.0194<0.05) and the value of thitung < ttable(-1.316 <1,676).